PROSPECTS OF PRODUCTION AND USE OF BUTAMINOFEN SUPPOSITORY FOR ANOGENITAL HERPES TREATMENT - M. E. Parkhach; O. I. Shadyro (Фармация и фармакология (Пятигорск), 2015)
The article shows theoretic substantiation of a butaminofen suppositories production reasonability – a new drug elaborated and synthesized in Belarus State University. We have considered the prospects of butaminofen suppositories use for anogenital herpes treatment. Evidence of a substance timeliness are based on the results of pharmacological, biopharmaceutical properties analysis of butaminofen and its marketing research.